2018
DOI: 10.1038/s41467-018-03007-3
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing catalyst heterogeneity by a  multifrequential oscillating reaction

Abstract: It is well documented that different surface structures of catalytically active metals may exhibit different catalytic properties. This is typically examined by comparing the catalytic activities and/or selectivities of various well-defined smooth and stepped/kinked single crystal surfaces. Here we report the direct observation of the heterogeneity of active polycrystalline surfaces under reaction conditions, which is manifested by multifrequential oscillations during hydrogen oxidation over rhodium, imaged in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 32 publications
(43 reference statements)
4
68
0
2
Order By: Relevance
“…Previous studies have reported the participation of perimeter or corner sites in CO oxidation and the WGSR . A novel explanation concerning the role of interfacial sites was that the surfaces of defects (steps and kinks) facilitated the formation of superficial oxygen, which sustained oscillations in the hydrogen oxidation activity at a polycrystalline Rh surface composed of crystals in microdomains of 10–50 μm with different orientations. Hence, in the case of the x PtAl samples, oxygen would be coordinated with the low coordination sites, which would be responsible for the CO activation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the participation of perimeter or corner sites in CO oxidation and the WGSR . A novel explanation concerning the role of interfacial sites was that the surfaces of defects (steps and kinks) facilitated the formation of superficial oxygen, which sustained oscillations in the hydrogen oxidation activity at a polycrystalline Rh surface composed of crystals in microdomains of 10–50 μm with different orientations. Hence, in the case of the x PtAl samples, oxygen would be coordinated with the low coordination sites, which would be responsible for the CO activation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, to assess the relative contributions of all pathways and to determine the rate limiting step, further studies would be required (e.g., by transient/concentration modulation IR spectroscopy 43 and detailed (micro)kinetic modeling). 23 25 …”
Section: Discussionmentioning
confidence: 99%
“…[26,27] These modifications can improve or inhibit the catalytic activity.I nc ontrast, poisoning hinders further reaction and reduces the number of available active sites. [26,27] These modifications can improve or inhibit the catalytic activity.I nc ontrast, poisoning hinders further reaction and reduces the number of available active sites.…”
Section: Layer 4: Active-site Modification and Poisoningmentioning
confidence: 99%